2014
DOI: 10.1002/sd.1570
|View full text |Cite
|
Sign up to set email alerts
|

Governing Fair Trade Coffee Supply: Dynamics and Challenges in Small Farmers' Organizations

Abstract: Farmers' organizations are essential actors in fair trade certification schemes, and therefore in delivering their associated benefits for poor small-scale farmers. However, the dynamics and challenges faced by these cooperative organizations have been largely bypassed in the fair trade literature. In this context, this paper aims to unpack the multiple, coexisting and interwoven marketing channels available for small-scale coffee producers, unveiling potential sources of uncertainty and tensions among competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Unlike Fair Trade, NAASA Organic certification does not require strong governance systems which would augment the social capital of the group (Hernandez-Aguilera et al, 2015;Ortiz-Miranda and Moragues-Faus, 2015). The CC2 group has low levels of social capital and lacks group cohesion leading to lower trust levels among members, especially between group leaders and ordinary members.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Fair Trade, NAASA Organic certification does not require strong governance systems which would augment the social capital of the group (Hernandez-Aguilera et al, 2015;Ortiz-Miranda and Moragues-Faus, 2015). The CC2 group has low levels of social capital and lacks group cohesion leading to lower trust levels among members, especially between group leaders and ordinary members.…”
Section: Case Studiesmentioning
confidence: 99%
“…NAASA Organic issued the group's certification, and its imposed governance system is weak. Unlike Fair Trade, NAASA Organic certification does not require strong governance systems which would augment the social capital of the group (Hernandez-Aguilera et al, 2015;Ortiz-Miranda and Moragues-Faus, 2015).…”
Section: Case Studiesmentioning
confidence: 99%
“…Exports + Imports GDP (9) The interpretation of the openness index is that the higher the index, the larger the influence of trade on domestic activities and the stronger the country's economy.…”
Section: Trade Openness =mentioning
confidence: 99%
“…by November 2013, fallen to the level of US$ 123 per pound [7]. Price volatility has wreaked drastic negative impacts on small producers in many developing countries [8,9]. Ironically, the disproportionate effects of the price volatility are mainly on the marginalized populations who make up a large population of coffee farmers, especially women and youths.…”
Section: Introductionmentioning
confidence: 99%
“…VSS has the potential to provide greater access to information and technology, via training, to help farmers improve the sustainability of production (Bray and Neilson, ). While some evidence indicates capacity building can improve livelihoods more effectively than price mechanisms (Ortiz‐Miranda and Moragues‐Faus, ), VSS tend to encourage farmers to specialise in coffee production (Vellema et al, ), which is problematic if it occurs at the expense of food production, diversified (and resilient) livelihoods or agro‐diversity (Barham and Weber, ; Stoian et al, ). Another recent systematic review of the effectiveness of certification schemes for improving socio‐economic outcomes (Oya et al, ) found that, although there was evidence for improvements in intermediate outcomes (producer prices and agricultural income), there was less evidence of impacts on endpoint outcomes (wages, household income and assets).…”
Section: Sustainability Programmes Value Chains and Rural Livelihoodsmentioning
confidence: 99%